Small deviation properties concerning arrays of non-homogeneous Markov information sources - Qin, Ximei; Rui, Zhaobiao; Chen, Shu; Peng, Weicai (Frontiers in Physics, 2023)
In this study, we first define logarithmic likelihood ratio as a measure between arbitrary generalized information sources and non-homogeneous Markov sources and then establish a class of generalized information sources for small deviation theorems, strong limit theorems, and asymptotic equipartition property. The present outcomes generalize some existing results.